The role of e-commerce in the urban food system under COVID-19: Lessons from China - Guo, Hongdong; Liu, Yehong; Shi, Xinjie; Chen, Kevin Z. (Emerald Publishing Limited, 2021)
The purpose of this study is to investigate e-commerce as a new means to ensure that the urban demand for food can be met during the coronavirus disease 2019 (COVID-19) outbreak. Because a number of COVID-19 e-commerce models have emerged, this paper discusses whether and (if so) why and how e-commerce can ensure the food supply for urban residents if social distancing becomes a norm and the transport and logistics systems are hindered.This study used qualitative research methods following the lack of empirical data. The authors referred to relevant literature, statistical data and official reports and comprehensively described the importance of e-commerce in ensuring the safety of food supply to Chinese urban residents under the impact of the epidemic. Corresponding to the traditional case study, this study presented a Chinese case on ensuring food supply through e-commerce during an epidemic.The authors found that three e-commerce models played a substantial role in preventing the spread of the epidemic and ensuring the food supply for urban residents. The nationwide e-commerce platforms under market leadership played their roles by relying on the sound infrastructure of large cities and its logistics system was vulnerable to the epidemic. In the worst-affected areas, particularly in closed and isolated communities, the local e-commerce model was the primary model, supplemented by the unofficial e-commerce model based on social relations. Through online booking, centralized procurement and community distribution, the risk of cross infection could be effectively reduced and the food demand could be effectively satisfied. The theoretical explanation further verifies that, apart from e-commerce, a governance system that integrates the government, e-commerce platform, community streets and the unofficial guanxi also impels the success of these models.Lessons from China are drawn for other countries struggling to deliver food to those in need under COVID-19. The study not only provides a solution that will ensure constant food supply to urban residents under the COVID-19 epidemic but also provides some reference for the maintenance of the food system of urban residents under the impact of a globalization-related crisis in future.